Photocatalytic hydrogen evolution by iridium(III)–rhodium(III) system: Effect of the free ligand addition. (30th January 2016) - Vasilchenko, D.B.; Tkachev, S.V.; Kurenkova, A. Yu.; Kozlova, E.A.; Kozlov, D.V.
Abstract: Rh(III) complexes of the general form RhL4 Cl2 with pyridine derivatives ligands (L) were used for the first time as water reduction catalysts in photocatalytic hydrogen generation process in pair with [Ir(ppy)2 bpy] + complex as a photosynthesizer. The efficiency of given Ir(III)–Rh(III) systems in the photocatalytic hydrogen generation process was found to be on the level of 20–30% which is corresponding to the highest currently achieved quantum efficiency values for homogeneous photocatalysts. Fast deactivation of the systems due to destruction of RhL4 Cl2 units was observed but it was suppressed via addition of extra amount of free L ligand in the reaction mixture. Quantum efficiency of modified in this manner [Ir(ppy)2 bpy] + /RhL4 Cl2 systems achieved up to 80% value. Graphical abstract: Highlights: New homogeneous Rh–Ir systems are efficient for photohydrogen production. Prolonged irradiation causes reduction of Rh to metal state and low activity. Addition of free ligands stabilizes system from decomposition. Quantum yield of 80% achieved by the stabilized systems.